Efecto de borde de la carretera Zungarococha en la densidad poblacional de Ranitomeya reticulata (anura: dendrobatidae) en el bosque del Huayo-Ciefor, Loreto, Perú - Sifuentes Garay, Fernando Junior (2024)
The Amazon has a great amphibian richness species and have been decimated by the destruction of their habitats due to the construction of roads, which generates an edge effect on their populations and subsequent local extinction. The study was made from may ton august 2023 with main objective of this work was to evaluate some ecological impacts of the Zungarococha highway on the population density of Ranitomeya reticulata (Anura: Dendrobatidae) department of Loreto, Peru. A sampling design using visual encounter survey was carried out from the edge of the road to 310 m. within the forest, which consisted of 10 plots of 30 x 30 m in the forests of the Center for Forestry Research and Education-CIEFOR. Data on the abundance of the species and the number of trees and the environmental variables of relative humidity (%) and temperature (°C) were obtained within each plot. Regression analysis, correlations and analysis of variance were performed between the variables under study. A positive and significant effect was recorded between the distance from the road and the abundance of Ranitomeya reticulata specimens (R2: 0.31) in at least 200 m. from the roadside; the correlation analysis between the abundance of trees and the population abundance of Ranitomeya reticulata was not significant and the regression analysis of relative humidity (%) and temperature (°C) had a significant effect (R2: 0.204 and (R2: -0.421) in the abundance of Ranitomeya reticulata specimens. Based on the resultswe concluded that there are negative ecological impacts of the Zungarococha highway on the population abundance of Ranitomeya reticulata (Anura: DENDROBATIDAE), being that there is a marked edge effect along with temperature and humidity in relation to the distance from the road It is necessary to implement a biological monitoring program in order to maintain fragmented populations of amphibian species in CIEFOR forests.